Crystallization and preliminary X‐ray diffraction analysis of the S‐adenosylhomocysteine hydrolase (SAHH) from Thermotoga maritima. Issue 11 (5th November 2014) - He, Miao; Zheng, Yingying; Huang, Chun‐Hsiang; Qian, Guojun; Xiao, Xiansha; Ko, Tzu‐Ping; Shao, Weilan; Guo, Rey‐Ting
<x xml:space="preserve">Abstract</x> S‐Adenosylhomocysteine hydrolase (SAHH) catalyzes the reversible conversion of S‐adenosylhomocysteine into adenosine and homocysteine. The SAHH from Thermotoga maritima (TmSAHH) was expressed in Escherichia coli and the recombinant protein was purified and crystallized. TmSAHH crystals belonging to space group C2, with unit‐cell parameters a = 106.3, b = 112.0, c = 164.9 Å, β = 103.5°, were obtained by the sitting‐drop vapour‐diffusion method and diffracted to 2.85 Å resolution. Initial phase determination by molecular replacement clearly indicated that the crystal contains one homotetramer per asymmetric unit. Further refinement of the crystal structure is in progress.